Cultivating Digital Fluency in Schools: Challenges and Sustainable Solutions - Anwar Dzikrullah; Fatimah Ramadhani; Prastio Efendi; Monoko Haguchi (JINEA: Journal of Innovation in Education and Learning, 2025)
This study examines the integration of digital fluency in educational systems through an integrative model combining technical, pedagogical, and equitable access dimensions. Using a narrative literature review of interdisciplinary sources (2020–2025), the research identifies key challenges: infrastructure gaps, pedagogical misconceptions (e.g., the "digital native" myth), and policy fragmentation. Findings highlight successful global practices, including 1:1 device program with offline capabilities (Uruguay), TPACK-based teacher training (South Korea), and community partnerships (Portugal). The proposed model emphasizes aligning DigComp 2.2 frameworks with localized strategies to address disparities, particularly in resource-constrained settings. Results demonstrate that holistic approaches, combining infrastructure investment, transformative pedagogy, and inclusive policies are essential for developing ethical, critical, and creative digital competencies. The study contributes actionable insights for policymakers and educators to bridge the digital fluency gap in diverse contexts.